Psoriasis and its association with serum lipid profile: A hospital-based case-control study - Pokhrel, Kumar; Shahi, Kamal Jung; Parajuli, Sudip (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Psoriasis is a chronic immune-mediated inflammatory dermatosis associated with significant cardiovascular comorbidity. Population-specific data on lipid abnormalities in Nepalese psoriasis patients are limited. This study aimed to determine the association of psoriasis with serum lipid profiles.Methods: This hospital-based case-control study enrolled 73 confirmed psoriasis cases and 73 age and sex-matched healthy controls. Fasting serum triglycerides, total cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol were measured. Disease severity was graded by the Psoriasis Area and Severity Index.Results: Psoriasis vulgaris was the commonest clinical pattern 40 (54.8%). Cases had significantly elevated median triglycerides (145.0 vs. 122.0 mg/dl; p